2019
DOI: 10.1177/1069397119861954
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Parental Control of Mate Choice, Opposition to Out-Group Mating, and Ethnic Identification in Surinam

Abstract: This study examined the attitude toward parental control of mate choice, and two potential factors related to this, that is, opposition to out-group mating and ethnic identification, in the five major ethnic groups from the Republic of Surinam (n = 500), that is, Hindustani, Creoles, Maroons, Javanese, and people of Mixed descent. Some of the main differences between groups were the following: Hindustani and Maroons had a more positive attitude toward parental control than all other groups, Hindustani were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…A previous analysis in this sample had shown that there are differences income level and educational level between the ethnic groups (Buunk et al, 2020). Income and educational level are highest among the Mixed, with minor differences between the other ethnic groups.…”
Section: Preliminary Analysesmentioning
confidence: 54%
See 1 more Smart Citation
“…A previous analysis in this sample had shown that there are differences income level and educational level between the ethnic groups (Buunk et al, 2020). Income and educational level are highest among the Mixed, with minor differences between the other ethnic groups.…”
Section: Preliminary Analysesmentioning
confidence: 54%
“…The present findings are also in line with other findings from the same sample that only among the Hindustani the majority was legally married, whereas this was only the case for less than 10% of the Maroons, with the figures for the Javanese and Mixed between these extremes. Among Maroons living together without being married was very common, but also among the Creoles, Javanese, and Mixed about a third or more were living together (Buunk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the Hindustani (70%) and the Javanese (61%), a substantial majority grew up in a family in which the father was present, whereas this occurred only for minorities of around 40% of the Creoles and Maroons. Finally, income and educational level were highest among the Mixed, with minor differences between the other ethnic groups (Buunk, Leckie & Pollack, 2019).…”
Section: Methodsmentioning
confidence: 98%
“…The present data came from a sample that consisted of 500 participants, aged 25 to 50 years, M = 36.56, SD = 7.79. Previous papers using data from this sample have focused on parental control over mate choice (Buunk, Leckie, & Pollack, 2020) and jealousy (Buunk, Dijkstra et al, 2020). There were about equal numbers of randomly selected participants in each ethnic group, that is, 102 Creoles (20.4%), 95 Hindustani (19.0%), 98 Javanese (19.6%), 102 Maroons (20.4%), and 103 people of mixed descent (20.6%).…”
Section: Methods Samplementioning
confidence: 99%